2019
DOI: 10.1177/0306624x19895976
|View full text |Cite
|
Sign up to set email alerts
|

Emotions, Affections, and Psychopathy Among Female Prisoners

Abstract: The present study intends to be a contribution to understand affections and emotions associated with female psychopathy. Although there are several studies aiming to understand psychopathy, there is still a gap in the integration of such a concept in affective dimensions, as well as a scarcity of surveys conducted in the female population. Sixty-three women confined to prison, located in the North region of Portugal, participated in this study. Participants were assessed using the Positive and Negative Affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 71 publications
(105 reference statements)
0
5
0
Order By: Relevance
“…As a result, research on psychopathy has historically relied heavily on samples of incarcerated males (Benning et al, 2018), often measured during risk assessment evaluations (Douglas et al, 2018; Hare et al, 2000; Leistico et al, 2008). Psychopathy is also present among females, although a majority of research indicates that in both institutionalized and noninstitutionalized samples, women demonstrate lower psychopathy scores compared to men (Pinheiro et al, 2020; Verona & Vitale, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, research on psychopathy has historically relied heavily on samples of incarcerated males (Benning et al, 2018), often measured during risk assessment evaluations (Douglas et al, 2018; Hare et al, 2000; Leistico et al, 2008). Psychopathy is also present among females, although a majority of research indicates that in both institutionalized and noninstitutionalized samples, women demonstrate lower psychopathy scores compared to men (Pinheiro et al, 2020; Verona & Vitale, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is also necessary to consider the use of self-report measures (Bäckström Taking into consideration the specifics of the present study, the evidence reported here indicates that the interaction of certain personality traits and human values may be indicative of antisocial conduct. However, it should also be remembered that the sample studied here was predominantly composed of women, who presented with a lower level of psychopathy than the men (Pinheiro et al, 2020;Verona & Vitale, 2018). It would be necessary to apply it to a sample with a more equitable representation of the sexes.…”
Section: Discussionmentioning
confidence: 90%
“…Literature also points that offenders high on psychopathy might be less likely to perceive a need for treatment due to their emotional deficits and their incapability to acknowledge their behavior as problematic (Cleckley, 1941;Pinheiro et al, 2019) and that women with higher scores in the interpersonal facet exhibit evidence of psychological resilience (Hicks et al, 2010). Thus, perhaps the opposite, i.e., low scores on the interpersonal facet were related to a higher perception of health needs and to a higher insight on their behaviors, which may lead them to seek for health services.…”
Section: Discussionmentioning
confidence: 99%
“…Although the research on psychopathy has been mainly conducted among male samples, evidence supports the psychopathy construct in female offender populations even if its behavioral manifestations are different from men (Rogers et al, 2007;Vaughn et al, 2008;Verona & Vitale, 2019). Psychopathy in women is less prevalent than in men (Beryl et al, 2014;Pinheiro et al, 2019) and psychopathic women's recidivism rate has been found to be lower than the recidivism rate among psychopathic men (Salekin et al, 1998). Studies suggest that manipulative women tend to flirt more often, while men tend to commit fraud (Forouzan & Cooke, 2005), tend to exhibit criminal behavior based on theft and fraud, whereas men generally engage in violence (Harris et al, 2007).…”
Section: Psychopathy and Prison Adjustmentmentioning
confidence: 99%